Gustatory epileptic aura: mesiotemporal versus insular localization? Case report studied with stereo-EEG - Barreto-Acevedo, Elliot (2025)
Gustatory epileptic auras are uncommon and have been described as locating ictal onset in the mesiotemporal region, insula or parietal operculum. We report the case of a patient with drug-resistant focal epileptic seizures, with limbic semiology and gustatory auras. After performing phase 1 of presurgical studies for epilepsy surgery, the patient was evaluated with stereo-EEG. The electroclinical findings and their analysis of spatiotemporal dynamics led to the conclusion that it was an epileptogenic network, with ictal onset in the mesiotemporal and left anterior insular (temporal plus) regions. The gustatory aura, when part of the early ictal semiology, suggests involvement of the insulo-opercular region in the ictal onset zone. The ictal origin of the patient's gustatory auras is discussed and a review of the related literature is performed.